Aspects Towards the Anastomotic Healing in Crohn’s Disease: Clinical Approach and Current Gaps in Research - Chaim, F.H.M.; Negreiros, L.M.V.; Steigleder, K.M.; Siqueira, N.S.N.; Genaro, L.M.; Oliveira, P.S.P.; Martinez, C.A.R.; Ayrizono, M.L.S.; Fagundes, J.J.; Leal, R.F. (Frontiers in Surgery, 2022)
Anastomotic leakage is a major complication in gastrointestinal and colorectal surgery and its occurrence increases morbidity and mortality. Its incidence is even higher in Crohn’s disease surgeries. Several authors have identified factors involved in the pathophysiology of anastomotic leak in the literature with the aim to reduce its occurrence and, hence, to improve its surgical treatment. Surgical technique is the most discussed topic in studies on guiding the performance of side-to-side stapled anastomosis. Preoperative nutritional therapy also has been shown to reduce the risk of anastomotic leakage. Other factors remain controversial – immunomodulator use and biologic therapy, antibiotics, and gut microbiota – with studies showing a reduction in the risk of complication while other studies show no correlation. Although mesenteric adipose tissue has been related to disease recurrence, there is no evidence in the literature that it is related to a higher risk of anastomotic leakage. Further exploration on this topic is necessary, including prospective research, to support the development of techniques to prevent anastomotic leakage. This will benefit Crohn’s disease patients who have to undergo a surgical procedure.